Sclerosing pneumocytoma mixed with a typical carcinoid tumor: A case report and review of literature. Issue 5 (February 2019) - Wang, Zhao; Yang, Mai-Qing; Huang, Wen-Jing; Zhang, Di; Xu, Hong-Tao
Abstract: Rationale: Sclerosing pneumocytoma accompanied with other type of tumor in one patient is very rare. Here, we report a case of a sclerosing pneumocytoma mixed with a typical carcinoid tumor in a same neoplasm. Patient concerns: A 55-year-old woman incidentally detected a space-occupying lesion of right lung in routine health examination. The patient was asymptomatic and there were no positive findings in routine laboratory examination, physical examination, and pulmonary function test. Computed tomography revealed a solitary round mass in the middle lobe of the right lung. Diagnosis: The lesion was diagnosed as a sclerosing pneumocytoma accompanied with a typical carcinoid tumor of the right lung. Intervention: The patient underwent thoracoscopic lobectomy in our hospital. Outcomes: The postoperative course was uneventful. Lessons: This case is rare and noteworthy for a lesion containing two different types of neoplasms, which may cause diagnostic difficulties.